Prediction Of Future Temperature And Rainfall Characteristics Using Statistical Downscaling Model (Sdsm) For Ibu Bekalan Jelai Station In Kurau River Basin - khalil, arif; Arish, Nuraini (Progress in Engineering Application and Technology, 2021)
Events of environmental change and its effects on the water cyclehave emerged in the last decades. Temperature and frequent variability aswell as rainfall and flow patterns are rising, due to the impacts of climatechange. Bukit Merah is the centre of tourism (Bukit Merah Laketown Resort)and farming (paddy irrigation). Nevertheless, climate change affects thisregion as it is affected by low dry seasonal water levels and high quantities ofmonsoon water causing floods. This work discusses the use of statisticaldownscaling model (SDSM) in the Bukit Merah reservoir to forecast theexpected rainfall and climate changes. The SDSM was optimized anddeveloped for future possible scenarios climate factors such as temperatureand precipitation use GCMs (global climate models). The study forecastestimated 10 years (2020-2030) of rainfall and temperature at the BukitMerah reservoir.